Contextual Inferencing Strategies and Changes in Reading Attitudes: the Case of Iranian EFL Undergraduates - Танназ Садегжи; Амін Марцбан (Психолінгвістика)
Objective. The present study examined the impact of contextual inferencing on Iranian EFL learners’ attitudes towards reading in English.